10-2x=3(x-2)+4

Simple and best practice solution for 10-2x=3(x-2)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-2x=3(x-2)+4 equation:


Simplifying
10 + -2x = 3(x + -2) + 4

Reorder the terms:
10 + -2x = 3(-2 + x) + 4
10 + -2x = (-2 * 3 + x * 3) + 4
10 + -2x = (-6 + 3x) + 4

Reorder the terms:
10 + -2x = -6 + 4 + 3x

Combine like terms: -6 + 4 = -2
10 + -2x = -2 + 3x

Solving
10 + -2x = -2 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
10 + -2x + -3x = -2 + 3x + -3x

Combine like terms: -2x + -3x = -5x
10 + -5x = -2 + 3x + -3x

Combine like terms: 3x + -3x = 0
10 + -5x = -2 + 0
10 + -5x = -2

Add '-10' to each side of the equation.
10 + -10 + -5x = -2 + -10

Combine like terms: 10 + -10 = 0
0 + -5x = -2 + -10
-5x = -2 + -10

Combine like terms: -2 + -10 = -12
-5x = -12

Divide each side by '-5'.
x = 2.4

Simplifying
x = 2.4

See similar equations:

| (3x-15)(24x-1200)=0 | | 3x=-9-18y | | e^3x=80 | | 3x+30=80 | | -9-11y= | | 3x=333 | | 5x^2+4=-9x | | (5-v)(5v+7)=0 | | 9y-2+8=3y+38+y | | -0.5(2)+3=y | | -0.5(0)+3=y | | z^4+(1-i)=0 | | -0.5(-2)+3=y | | 7t-(6-5t+(3t+4))= | | 25+13.5h-0.25h= | | t=25+13.5h-0.25h | | 2(7-z)= | | 5z-14= | | 65-6x=8 | | 1x^2-49=0 | | -9(x+5)=82 | | m^2-33n+1=0 | | X^2-12+30=0 | | 6r+4=s^2 | | -4cos^2x-2cosx-3=0 | | 2x^2+6x+20=0 | | -2.5x+5= | | -2=5x-37 | | 3(8+r)=3r-27 | | 2r-7=3r-14 | | 6(r+5)=r+30 | | 6g+4(-7+4g)=1-g |

Equations solver categories